The role of obestatin in roux‐en‐Y gastric bypass‐induced remission of type 2 diabetes mellitus. Issue 6 (20th November 2015) - Wang, Jian‐li; Xu, Xian‐hui; Zhang, Xue‐jun; Li, Wei‐hua
Summary: Type 2 diabetes mellitus (T2DM) is a complex and multifactorial disease that is generally characterized by insulin resistance and loss of β‐cell function that develops in adulthood. To date, more than 6% of the world's population is affected by T2DM. The main treatments of T2DM are dietary and lifestyle changes. However, only dependent on behaviour modification and oral hypoglycemics, many patients are unable to maintain glycemic control. Emerging evidence indicates that up to 80% of patients with T2DM undergoing Roux‐en‐Y gastric bypass (RYGB) experience complete remission of their T2DM and the majority of remissions occur almost immediately following the operation. Obestatin is a 23‐amino‐acid peptide, which is not only thought to suppress food intake and decrease gastric emptying but also found to exert survival effects in pancreatic β cells, increase glucose‐stimulated insulin secretion, and reduce insulin resistance and inflammation. In addition, some researchers demonstrated that obestatin is a nutritional marker reflecting body adiposity and insulin resistance. Although results from previous studies were conflicting, the peripheral blood concentrations of obestatin were changed after RYGB. Therefore, regulation of obestatin level may be another mechanism for RYGB‐induced remission of T2DM. In this article, we review briefly the effect of RYGB on T2DM in humans and offer an overview of the published data on the effects of RYGB on obestatin level in patients with T2DM. Furthermore, the possible roles of obestatin in the remission of T2DM following RYGB are also reviewed. Copyright © 2015 John Wiley & Sons, Ltd.